OIRAD – THE PRESTIGE LANGUAGE: Ethnolinguistic Approach to the Altai Oirad Language and its Dialects - Birtalan Ágnes (Acta Mongolica, 2013)
The phenomenon and the approach In order to introduce the discussion of the phenomenon and to avoid some unnecessary misunderstandings as the approach indicated in the title could be comprehended in different ways as well, it is inevitable to establish and expose the frame how it is implied concerning the Altai Oirad language on the basis of my fieldwork material.